2021
DOI: 10.3390/pharmaceutics13071047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design Based Optimization and Ex Vivo Permeation of Desmopressin Acetate Loaded Elastic Liposomes Using Rat Skin

Abstract: The study aimed to develop elastic-liposome-based transdermal delivery of desmopressin acetate for enhanced permeation to control enuresis, central diabetes insipidus, and traumatic injury. Elastic liposomes (ELs)-loaded desmopressin acetate was prepared, optimized, and evaluated for improved transdermal permeation profiles using rat skin. Full factorial design with independent factors (X1 for lipid and X2 for surfactant) at three levels was used against four responses (Y1, Y2, Y3, and Y4) (dependent variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The hemolytic activity of nanocarriers is an important preliminary assessment of their toxicity [62]. This analysis is used to evaluate the destruction degree of red blood cells in the presence of chitosomes.…”
Section: Analysis Of Hemolytic Activity and Cytotoxicitymentioning
confidence: 99%
“…The hemolytic activity of nanocarriers is an important preliminary assessment of their toxicity [62]. This analysis is used to evaluate the destruction degree of red blood cells in the presence of chitosomes.…”
Section: Analysis Of Hemolytic Activity and Cytotoxicitymentioning
confidence: 99%
“…Caffeine has the smallest molecular weight, therefore can easily pass through skin into the donors compartment in comparison to larger molecular weight catechins. The permeation parameters tested included permeation flux (J, µg/cm 2 /h) was calculated as the slope obtained from the linear portion of the plot divided by the skin surface area (Adhikari et al, 2010 ), and enhancement ratio which is a ratio of the flux value of the chosen optimum formulation to the flux value of drug solution (Hussain et al, 2020 ; Altamimi et al, 2021 ). Formula (N8) showed a flux value of 0.1201 µg/cm 2 /h and an enhancement ratio of 0.12 which were relatively low along with sustained release profile with a lag time of 8.72 hr, which indicated that the selected formula was present at the site of action.…”
Section: Resultsmentioning
confidence: 99%
“…The MTT assay and the hemolysis test (n=3) were employed, as stated in a study that we had previously published. 31,32 HG-HUVECs and LPS stimulated RAW264.7 cells were incubated with Cunps at different concentrations for 24 hours, respectively. After incubation with serum-free medium containing MTT for 4 hours, DMSO solution was added to each well and the absorbance was measured at 490 nm.…”
Section: Synthesis and Characterization Of Cunpsmentioning
confidence: 99%